Legal Politics Of Higher Education Creative Media To Support The Creative Industry In The Era Of The Industrial Revolution 5.0 - H, RR. Ella Evrita; Rahayu, Mella Ismelina Farma; Asrun, Andi Muhammad; Lubis, Efridani (University of Merdeka Malang, 2023)
This article discusses that the current legal politics have regulated higher education and creative industries but have not accommodated all the needs for their implementation, especially now when the industrial revolution 5.0 will occur. Through the right legal political policies, creative media higher education can be the key in supporting the development of the creative industry in the era of the Industrial Revolution 5.0, to create a favorable and innovative environment for creative industry players. The type or type of research chosen, namely normative juridical. The point of view of this research will be focused on